The impact of quality of public administration on local economic growth in Vietnam - Thanh Hung Pham; Thi Thanh Hang Hoang; Eleftherios Thalassinos; Hoang Anh Le (Journal of Risk and Financial Management, 2022)
This study examines how the quality of public administration influenced local economic growth in Vietnam from 2011 to 2019. Based on previous studies, we evaluate this impact through the Cobb-Douglas function includes government capital, thereby examining both the individual and interactive effects of local government expenditures and quality of public administration on local economic growth in Vietnam. The system GMM method (SGMM) was used to estimate the model with data collected from 61 provinces and cities in Vietnam in the period 2011-2019. The findings suggest that local government expenditures and quality of public administration positively influence local economic growth in Vietnam. Thereby, the authors propose policy implications to improve the efficiency of local government expenditures on local economic growth in Vietnam in terms of public administration.
Keywords: 330; quality of public administration; local government expenditures; economic growth; PAPI index; SGMM